‘I don’t understand everything here ... I’m scared’: Discontinuities as experienced by first-year education students in their encounters with assessment - Shalem, Y.; Dison, L.; Gennrich, T.; Nkambule, T. (South African Journal of Higher Education, 2016)
The authors examine students perceptions of the written assessment tasks in a BEd first-year course. The article is an attempt to engage seriously with student perceptions of the various elements of assessment, and to make explicit their understanding of the textual forms appropriate for academic writing. The analysis presented in this article draws on data gathered from three focus-group discussions with 18 first-year students about their experiences of assessment and shows that behind what appears as a lack of understanding of basics, such as referencing rules, lies a misrecognition of the textual forms appropriate for academic writing, in short, of academic criteria. We use the notion of discontinuity to describe the difficulty students experience (particularly low-achieving students) regarding academic writing in comparison to their experiences of school writing. The analysis demonstrates three different discontinuities. Firstly, in comparison to school writing all the students, but particularly the average and the low-achieving students, experience the requirement to position themselves in relation to knowledge authorities as constraining. Secondly, in comparison to school writing, academic writing foregrounds focus, elaboration and justification, which are criteria that only the high-achieving students in the group understood as necessary in order for one to know what something is. Thirdly, in view of their misrecognition of academic criteria (by focusing on content alone rather than on content and form), the average and the low-achieving students struggle to judge their lecturers feedback on their writing. Conceptually, the discontinuities reflect the gap between the form of writing the students think they need to follow and the textual forms they are expected to produce.